Determination of Community Structure and Diversity of Seed-Vectored Endophytic Fungi in Alpinia zerumbet - Yan, Kuan; Pei, Zihao; Meng, Lina; Zheng, Yu; Wang, Lian; Feng, Ruizhang; Li, Quanzi; Liu, Yang; Zhao, Xianming; Wei, Qin; El-Sappah, Ahmed H.; Abbas, Manzar (Frontiers in Microbiology, 2022)
Endophytic fungi act as seed endosymbiont, thereby playing a very crucial role in the growth and development of seeds. Seed-vectored endophytic fungi establish an everlasting association with seeds and travel from generation to generation. To explore the composition and diversity of endophytic fungi in Alpinia zerumbet seeds, high throughput Illumina MiSeq sequencing was employed for the following stages: fruit formation period (YSJ1), young fruit period (YSJ2), early mature period (YSJ3), middle mature period (YSJ4), and late mature period (YSJ5). A total of 906,694 sequence reads and 745 operational taxonomic units (OTUs) were obtained and further classified into 8 phyla, 30 classes, 73 orders, 163 families, 302 genera, and 449 species. The highest endophytic fungal diversity was observed at YSJ5. The genera with the highest abundance were Cladosporium, Kodamaea, Hannaella, Mycothermus, Gibberella, Sarocladium, and Neopestalotiopsis. FUNGuild analysis revealed that endophytic fungi were undefined saprotroph, plant pathogens, animal pathogen-endophyte-lichen parasite-plant pathogen-wood saprotroph, and soil saprotrophs. Alternaria, Fusarium, Cladosporium, and Sarocladium, which are potential probiotics and can be used as biocontrol agents, were also abundant. This study is part of the Sustainable Development Goals of United Nations Organization (UNO) to “Establish Good Health and Well-Being.”